The theory on homogeneous micro-fluid mixtures - Diep, Nguyen Van; Chanh, Truong Minh (Vietnam Journal of Mechanics, 1979)
This paper deals with the construction x of a generalized- diffusive theory of simple micro-fluid mixtures composed of a reactive constituents in the relative motion to one another and treated as a single simple micro-fluid. The basic laws of balance are given by postulating the balance law of energy together with invariant requirement under superposed rigid body motions or the mixture as a whole. The linear or nonlinear constitutive equations and full thermodynamic restrictions are given.